1977
DOI: 10.1136/adc.52.7.591
|View full text |Cite
|
Sign up to set email alerts
|

Hypoglycaemia in congenital adrenal hyperplasia.

Abstract: Two young children with salt-losing congenital adrenal hyperplasia developed profound hypoglycaemia. In one child hypoglycaemia occurred after a prolonged fast and in the other it was precipitated by infection. This complication may be more common than the literature suggests, and emergency treatment with glucose or hydrocortisone, given by injection, should be given to any child with the disorder who suddenly or unexpectedly collapses.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

1982
1982
2016
2016

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 3 publications
(4 reference statements)
0
6
0
Order By: Relevance
“…However, an explanation is more difficult for several cases of symptomatic hypoglycemia, which occurred despite plausible documentation of compliance with treatment and sick day rules. The prevention of severe hypoglycemia seems not to be completely covered by the current treatment recommendations, although there are reports of hypoglycemia (35,36,37,38,39,40) and adrenomedullary dysfunction (2,41,42) in limited CAH study populations. For example, in a French cohort of 45 children diagnosed with classic CAH between 1981 and 1997, at ages 1-5 years and already under treatment, eight patients had severe hypoglycemic events, two of them lethal, while only three patients had a salt-wasting crisis (18).…”
Section: Discussionmentioning
confidence: 99%
“…However, an explanation is more difficult for several cases of symptomatic hypoglycemia, which occurred despite plausible documentation of compliance with treatment and sick day rules. The prevention of severe hypoglycemia seems not to be completely covered by the current treatment recommendations, although there are reports of hypoglycemia (35,36,37,38,39,40) and adrenomedullary dysfunction (2,41,42) in limited CAH study populations. For example, in a French cohort of 45 children diagnosed with classic CAH between 1981 and 1997, at ages 1-5 years and already under treatment, eight patients had severe hypoglycemic events, two of them lethal, while only three patients had a salt-wasting crisis (18).…”
Section: Discussionmentioning
confidence: 99%
“…Hypoglycaemia is a frequent finding in all cortisol deficiency states [1,5,7,8,10,14], suggesting the same pathogenesis of the hypoglycaemia. It is interesting to note that the associated hypoalaninaemia and low catecholamine secretion in our patient (which has not been described previously in isolated glucocorticoid deficiency), have been previously reported in isolated ACTH deficiency [1].…”
Section: Discussionmentioning
confidence: 97%
“…There are several reports of hypoglycemia in children with CAH associated with acute illness episodes (Mackinnon & Grant, 1977). Pinto (Pinto et al, 2003) reported the follow-up of 68 children with classic CAH, and noted that hypoglycemia occurred 9 times in children between the ages of 1 to 3 years, and resulted in two deaths.…”
Section: Discussionmentioning
confidence: 99%